Forces that interfere in the school's confrontation of child violence (Research, Society and Development, 2020)
The objective of this research was to identify forces that interfere in the school's confrontation of child violence, through the assumptions of the Force Field Theory. For this, a methodological approach of the qualitative type was used and teachers from a public school in Palmas, Tocantins, Brazil, were interviewed. It was identified that although the school is part of the School Health Program (SHP), it does not carry out actions to curb childhood violence. Among the forces that act in such a way as to restrict child protection, the following have been highlighted: lack of resolution of other services that make up the network; family breakdown; ignorance of the role in the network; misconduct; lack of articulation between child protection services; the biologicist model of health care; and neglect of the role in the network. It is concluded that there is no implementation of integrated actions by the health and education sectors, in order to prevent and interrupt cases of violence against children.